Hippocampal Volume as a Putative Marker of Resilience or Compensation to Minor Depressive Symptoms in a Nonclinical Sample - Besteher, Bianca; Squarcina, Letizia; Spalthoff, Robert; Bellani, Marcella; Gaser, Christian; Brambilla, Paolo; Nenadić, Igor (Frontiers in Psychiatry, 2019)
Case-control studies in major depression have established patterns of regional grey matter loss, including the hippocampus, which might show state-related effects dependent on disease stage. However, there is still limited knowledge on compensation effects that might occur in people resilient to depression showing only subclinical symptoms. We used voxel-based morphometry on a multi-centre data set of 409 healthy non-clinical subjects to test the hypothesis that local hippocampal volume would be inversely correlated with subclinical depressive symptoms (SCL90R depression scores). Our region-of-interest results show a significant (p=0.042, FWE cluster-level corrected) positive correlation of SCL90R scores for depression and a left hippocampus cluster. Additionally, we provide an exploratory finding of gyrification, a surface-based morphometric marker, correlating with a right postcentral gyrus cluster (p=0.031, FWE cluster-level corrected). Our findings provide first preliminary evidence of an inverse relationship for subjects in the absence of clinical depression, and might thus point to processes related to compensation. Similar effects have been observed in remission from major depression and thus deserve further study to evaluate hippocampal volume not only as a state-dependent marker of disease but also of resilience.